Fusobacterium necrophorum from pericoronitis resulting in disseminated intravascular coagulation: a case report and review of literature. Issue 1 (January 2016) - Basavarajappa, Santhosh; Durgesh, Bangalore H.; Ramakrishnaiah, Ravikumar; Al Kheraif, Abdulaziz A.; Divakar, Darshan Devang
Abstract : It has been reported that complication due to Fusobacterium necrophorum may lead to disseminated intravascular coagulation associated with septicaemia, capable of platelet aggregation and coagulation factor activation. Here, we present a case report of a 43-year-old male patient with F. necrophorum pericoronitis, followed by septicaemia and disseminated intravascular coagulation. The patient was treated with intravenous metronidazole and imipenem, and recovered thereafter.